Hydrogen Rich Water Improved Ventilatory, Perceptual and Lactate Responses to Exercise - Botek, Michal; Krejčí, Jakub; McKune, Andrew J; Sládečková, Barbora; Naumovski, Nenad (International journal of sports medicine, 2019)
The potential anti-fatigue and performance benefits of hydrogen rich water (HRW) have resulted in increased research interest over the past 5 years. The aim of this study was to assess physiological and perceptual responses to an incremental exercise protocol after administration of 600 ml HRW within 30 min before exercise. This randomized, double blinded placebo-controlled cross over study included twelve healthy males aged 27.1±4.9 years. The exercise protocol consisted of a 10 min warm-up at 1.0 W.kg-1, followed by 8 min at 2.0, 3.0, and 4.0 W.kg-1, respectively. Cardio-respiratory variables, lactate and ratings of perceived exertion (RPE) were assessed in the last minute of each step. A significantly lower blood lactate was found with HRW (4.0±1.6 and 8.9±2.2 mmol.l-1) compared to Placebo (5.1±1.9 and 10.6±3.0 mmol.l-1) at 3.0, and 4.0 W.kg-1, respectively. Ventilatory equivalent for oxygen and RPE exhibited significantly lower values with HRW (32.3±7.2, and 17.8±1.2 points, respectively) compared to Placebo (35.0±8.4, and 18.5±0.8 points, respectively) at 4 W.kg-1. To conclude, acute pre-exercise supplementation with HRW reduced blood lactate at higher exercise intensities, improved exercise-induced perception of effort, and ventilatory efficiency.
Keywords: dospělí; Physical Exertion; pití; vodík; Adult; Perception; mladý dospělý; Lactic Acid; kyselina mléčná; svalová únava; Oxygen Consumption; percepce; lidé; dvojitá slepá metoda; cvičení; Respiration; voda; srdeční frekvence; dýchání; Hydrogen; Water; Double-Blind Method; Male; Muscle Fatigue; Young Adult; tělesná námaha; mužské pohlaví; Exercise; Heart Rate; spotřeba kyslíku; Drinking; Humans